1999
DOI: 10.1016/s0735-1097(99)00095-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naloxone on myocardial ischemic preconditioning in humans

Abstract: The adaptation to ischemia observed in humans after two sequential coronary balloon inflations is abolished by naloxone and is independent of collateral recruitment. Thus, it is due to ischemic preconditioning and is, at least partially, mediated by opioid receptors, suggesting their presence in the human heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 46 publications
0
60
0
3
Order By: Relevance
“…At the end of each balloon inflation, the intensity of anginal pain was assessed using a visual analog scale. 18 Patients were asked to place a mark on a scale of 10 ranging from no pain (0) to the most severe pain ever experienced (10).…”
Section: Assessment Of Chest Painmentioning
confidence: 99%
“…At the end of each balloon inflation, the intensity of anginal pain was assessed using a visual analog scale. 18 Patients were asked to place a mark on a scale of 10 ranging from no pain (0) to the most severe pain ever experienced (10).…”
Section: Assessment Of Chest Painmentioning
confidence: 99%
“…22 Finally, early results suggest that opioid receptors also seem to play a role in preconditioning during coronary angioplasty. In fact, morphine sulfate 27 and naloxone 28 have, respectively, been shown to mimic and prevent the adaptation to ischemia during repeated balloon inflations.…”
Section: Mechanisms Of Ischemic Preconditioningmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] Previous studies have found that intravenous pre-administration of nicorandil attenuates ST-segment elevation 12) and improves lactate metabolism 13) during coronary angioplasty, suggesting that pharmacological preconditioning is induced by nicorandil. Troponin T (TnT) is one of the reliable metabolic markers of myocardial injury.…”
mentioning
confidence: 99%